Legal Implications Of Software Abuse Artificial Intelligence in Photo and Video Editing - Arung Rahmat Sijaya; Ivan Zairani Lisi; Alfian Alfian (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid advancement of knowledge and information technology has reshaped the perspectives and lifestyles of Indonesian citizens, particularly through innovations like Artificial Intelligence (AI), which automates various tasks and simplifies human activities. However, the misuse of AI has become a critical issue in 2023, especially in spreading sophisticated fake information. To address this, Law No. 1 of 2024, amending Law No. 11 of 2008 on Information and Electronic Transactions, is expected to combat AI software misuse effectively. This study investigates the legal implications of AI misuse, particularly concerning privacy and personal data security, and examines its interpretation under Articles 27 and 32 of the Information and Electronic Transactions Law to enhance law enforcement and safeguard individual privacy rights. Using a normative legal research approach, the findings reveal that AI misuse, such as manipulating photos and videos, violates data protection laws, including the GDPR in the European Union and Indonesia’s Personal Data Protection Act. Such violations can lead to severe penalties, legal consequences, and reputational damage for companies. Recognized as a form of cybercrime, AI misuse is addressed under Article 35 of the Information and Electronic Transactions Law, which provides a specialized legal framework for handling such offenses comprehensively.